Legume-based cover crop mixtures can overcome trade-offs between C inputs, soil mineral N depletion and residual yield effects - Engedal, Tine; Karlsson, Michelle; Andersen, Maria Skovgaard; Rasmussen, Jim; Thorup-Kristensen, Kristian; Jensen, Lars Stoumann; Magid, Jakob; Hansen, Veronika (Agriculture, ecosystems & environment, 2023)
Cover crops can contribute to climate change mitigation through enhanced sequestration of atmospheric carbon dioxide into soil organic carbon. Few studies, however, have estimated the total carbon (C) input to soil, i.e. derived both from plant material (shoot and root) and phyllo- and rhizodeposition. Selection of cover crop species should account for multiple objectives, such as C inputs to soil, nitrate leaching reduction and positive residual effects on the following main crop. However, trade-offs between these objectives may occur. The aim of this study was to investigate the performance of the cover crop species winter rye, hairy vetch and oilseed radish, and to assess the ability of mixtures to overcome potential trade-offs. A randomized split-plot field trial was conducted to compare cover crop treatments and a weeded control under high and low soil nitrogen (N) availability. Multiple-pulse labeling with 14C-CO2 was carried out to trace net cover crop-derived rhizodeposition C. Soil mineral N was measured to 1.5 m depth in autumn, as well as grain and N yield in the subsequent spring barley. Cover crop species accumulated between 1250 and 2580 kg C ha−1, with significantly higher total C input (in shoot, root and phyllo- and rhizodeposits) for the mixtures compared with pure stands of either vetch or radish, while the results for rye were in between. The quantity of C lost via phyllo- and rhizodeposition (qClvPR) showed a significant positive correlation with root C and was highest for the mixtures and rye. The relative ClvPR ranged between 7% and 14% of total cover crop-derived C and tended to decrease under higher soil N availability. All cover crop treatments were able to decrease soil mineral N (0–1.5 m), with radish displaying the highest N leaching reduction potential. Despite substantial differences in cover crop total N uptake and C:N ratios, no significant differences were observed in the subsequent main crop grain or N yields. The mixtures showed the highest total C input and generally a higher or similar mineral N depletion potential than the average of the pure stands, suggesting that cover crop mixtures offer a realistic means for overcoming trade-offs among ecosystem functions. •Winter rye and cover crop (CC) mixtures produced highest total and rhizodeposition C.•Root C was the strongest predictor of rhizodeposition C.•Oilseed radish depleted soil mineral N better than winter rye and hairy vetch.•CC mixtures depleted soil mineral N as well or better than the pure stand average.•Despite dissimilar CC quantity and quality, no crop yield effect of CCs was observed.